2014
DOI: 10.1071/wf13115
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and mapping dynamic variability in large fire probability in the lower Sonoran Desert of south-western Arizona

Abstract: In the lower Sonoran Desert of south-western Arizona, climate change and non-native plant invasions have the potential to increase the frequency and size of uncommon wildfires. An understanding of where and why ignitions are more likely to become large fires will help mitigate the negative consequences of fire to native ecosystems. We use a generalised linear mixed model and fire occurrence data from 1989 to 2010 to estimate the relative contributions of fuel and other landscape variables to large fire probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 31 publications
1
26
1
Order By: Relevance
“…It has been shown that lower elevation and flatter areas correlate positively with fire occurrence [62,63]. This is the case in many regions of China [30], as the majority of people reside at lower elevations in the Chinese boreal forest, and the same findings have been reported elsewhere [64][65][66]. Elevation likely influences fire frequency through surfacemoisture [67], species composition [68], and fuel moisture [69], which have been shown to increase with elevation.…”
Section: Discussionsupporting
confidence: 53%
“…It has been shown that lower elevation and flatter areas correlate positively with fire occurrence [62,63]. This is the case in many regions of China [30], as the majority of people reside at lower elevations in the Chinese boreal forest, and the same findings have been reported elsewhere [64][65][66]. Elevation likely influences fire frequency through surfacemoisture [67], species composition [68], and fuel moisture [69], which have been shown to increase with elevation.…”
Section: Discussionsupporting
confidence: 53%
“…Although our study occurred within the Mojave Desert, it is likely the burn severity pathway leading to long-term dominance of burned areas by invasive grasses occurs in other deserts in North America. Invasive plants have been widely implicated in the increased number and/or size of fires in the Great Basin and Sonoran Desert (Brooks & Pyke 2001;Balch et al 2013;McDonald & McPherson 2013;Gray, Dickson & Zachmann 2014), and the grass/fire cycle has been the main focus as the process responsible for the formation of alternative states. Prior to this study, it might have been thought that burned areas in the North American deserts that had longer fire return intervals were less likely to become dominated by invasive grass, but this may often not be the case.…”
Section: Discussionmentioning
confidence: 99%
“…Landscape conductance in a circuit-theoretic model is a surrogate for the ease of movement through the modeled environment (McRae et al 2008), and we begin by parameterizing the conductance surface for fire spread. Logistic regression models are commonly used to derive continuous maps of the conditional probability that an ignition occurrence will become a large fire (e.g., Preisler et al 2011, Hawbaker et al 2013, Gray et al 2014. The probabilities reflect an isolated likelihood that an ignition will result in a fire of at least some observed size, and do not account for fire spread dynamics beyond that specific location and size threshold.…”
Section: Modeling Fire Connectivitymentioning
confidence: 99%
“…Conditions for large fire occurrence are rare in our study area and we were primarily concerned with a worst-case scenario of fire likelihood, which we represented with conditions of high fire hazard (Hardy 2005). To model fire likelihood under high fire hazard, we first used a spatial database of fire occurrence spanning 22 years, multiple phenometric and other landscape variables, and mixed-effects logistic regression to estimate the conditional probability of a large (!20 ha) fire (Gray et al 2014). We chose 20 ha as the large fire size threshold because fires of this size are a good indication that the annual fuel load is sufficient for further fire spread (W. Reaves, personal communication).…”
Section: Estimating Fire Likelihoodmentioning
confidence: 99%
See 1 more Smart Citation